Transformasi Pesantren Dalam Perubahan Sosial: (Studi Pondok Pesantren Mi’rajussibyan NW Selanglet) - Fatmawati Fatmawati (Sekolah Tinggi Agama Islam al-Amin, Gersik, Kediri, Lombok Barat, NTB, 2019)
The birth of Islamic boarding schools in Indonesia has been a long process in accordance with the culture and traditions of this nation since before the era of independence. Islamic boarding schools which at the beginning of their existence only taught Islamic religious knowledge, improved and adapted to the surrounding environment to meet the demands of the community's needs. This paper examines in more depth the transformation of the Mi'rajussibyan Islamic Boarding School NW Selanglet into a madrasa. This research is a field research using a qualitative, sociological and historical approach. The researcher found that the transformation of Mi'rajussibyan Islamic Boarding School NW Selanglet into a Madrasah was to maintain its existence and expand its social role in the life of the Selanglet community which continues to change. The existence of the Mi'rajussibyan Islamic Boarding School in NW Selanglet has significant positive implications for the socio-economic changes of the surrounding community. The causes of the transformation include the demands of a free market economy, the politicization of education, a shift in the orientation of public education, and the modernization of Islamic boarding schools institutions, the expansion of the roles and social functions of Islamic boarding schools, and the inclusiveness of figures towards modernism in Islamic boarding schools.